Polyimide encapsulation of spider-inspired crack-based sensors for durability improvement - Kim, Taewi; Lee, Taemin; Lee, Gunhee; Choi, Yong Whan; Kim, Sang Moon; Kang, Daeshik; Choi, Mansoo (Applied Sciences (Switzerland), 2018)
In mechanical sensory systems, encapsulation is one of the crucial issues to take care of when it comes to protection of the systems from external damage. Recently, a new type of a mechanical strain sensor inspired by spider's slit organ has been reported, which has incredibly high sensitivity, flexibility, wearability, and multifunctional sensing abilities. In spite of many of these advantages, the sensor is still vulnerable in harsh environments of liquids and/or high temperature, because it has heat-vulnerable polyethylene terephthalate (PET) substrate without any encapsulation layer. Here, we present a mechanical crack-based strain sensor with heat, water and saline solution resistance by alternating the substrate from polyester film to polyimide film and encapsulating the sensor with polyimide. We have demonstrated the ability of the encapsulated crack-based sensor against heat, water, saline solution damage through experiments. Our sensor exhibited reproducibility and durability with high sensitivity to strain (gauge factor above 10,000 at strain of two percent). These results show a new potential of the crack-based sensory system to be used as a wearable voice/motion/pulse sensing device and a high-temperature strain sensor.
Keywords: Crack; Encapsulation; Spider inspired; Strain sensor; Thin metal film